Mastering the elements of kettlebell lifting in the context of developing a high level of a future healthy lifestyle within the vocational training process - S. , Derevenets; V. , Litovchenco; P. , Baranov (Problems of Engineer-Pedagogical Education, 2021)
The article researches the issues of mastering the elements of kettlebell lifting in the process of physical education in higher education for using it in further professional activities. The relevance of the problem is in the fact that, in contrast to other methods of achieving physical activity, the use of low-weight kettlebells in combination with exercises with simple ordinary household items is the most accessible and effective. The article focuses on the development of individual health programs with the inclusion of an assessment model of the level of physical health. Recommended health programs have been developed for subsequent use in practical professional activities. The systematization of motor loads for different age groups and health status is also considered. The typification of physical exercises, depending on the level of intensity of their implementation, allows optimizing the program of motor activity. The technique of qualimetric assessment and self-assessment of the level of physical health, based on the individual capabilities of the individual and allowing control over the process of forming the optimal level of health, is proposed.